Prevention of firearm injuries with gun safety devices and safe storage: An Eastern Association for the Surgery of Trauma Systematic Review. Issue 6 (June 2018) - Violano, Pina; Bonne, Stephanie; Duncan, Thomas; Pappas, Peter; Christmas, A. Britton; Dennis, Andrew; Goldberg, Stephanie; Greene, Wendy; Hirsh, Michael; Shillinglaw, William; Robinson, Bryce; Crandall, Marie
Abstract : BACKGROUND: Over 50, 000 homicides and suicides occur each year. An estimated half of all US households are believed to have a firearm present, making them one of the most ubiquitous consumer products. Our goal was to determine if the manner of storage of a firearm in a home could potentially make a difference in the outcomes of intentional and unintentional injuries involving a firearm; specifically addressing the use of gun safes and devices that block/disable firearm function (trigger locks, cable locks, etc.). METHODS: A comprehensive review of the literature was performed. We used Grading of Recommendations Assessment, Development, and Evaluation methodology to assess the breadth and quality of the data specific to our Population, Intervention, Comparator, Outcomes (PICO) questions. RESULTS: A total of 176 studies were initially identified, then, 120 more added after a subsequent literature review, with 97 removed as duplicates. One hundred ninety-one case reports, case series, and reviews were removed because they did not focus on prevention or did not address our comparators of interest. This left a total of two studies which merited inclusion for PICO 1, should gun locks be used to prevent firearm injuries and six studies which merited inclusion for PICO 2, should safe storage for guns be used to prevent firearm injuries. CONCLUSION: PICO 1: We conditionally recommend that gun locks be used to prevent unintentional firearm injury. PICO 2: Because of the large effect size and the reasonable quality of available evidence with safe storage of firearms, we recommend safe storage prevent firearm-related injuries. LEVEL OF EVIDENCE: Systematic review, level III.